Architectural Design of Public Spaces in Realizing Good Urban Governance Based on Community Participation - Tiara Aditia; Anabel Landa Vazquez; Rafinita Aditia (Journal Governance Society, 2025)
Urban governance in rapidly transforming cities is increasingly challenged by declining civic engagement, social polarization, and the commodification of public spaces, yet governance debates often overlook how spatial and architectural conditions shape the possibility of meaningful participation. This study aims to conceptualize how the architectural design of public spaces functions as a mediator of good urban governance by embedding principles of transparency, inclusivity, participation, and accountability into the material fabric of the city. Employing a qualitative descriptive design with a literature based approach, the research synthesizes 40 core sources selected from 75 initial publications spanning governance studies, urban design, spatial theory, and architecture. Through qualitative content analysis and thematic synthesis, the study identifies key linkages between spatial design elements such as openness, accessibility, flexibility of use, co-management, and adaptive reuse and governance outcomes related to civic trust, social cohesion, and participatory decision-making. Case illustrations from cities including Copenhagen, Bandung, Seoul, Cagliari, Luanda, and mid-sized Indonesian cities show that participatory and inclusive public space design can enhance collaborative governance, while exclusionary or heavily securitized spaces undermine it. The analysis also highlights constraints such as unequal participation, bureaucratic silos, limited resources, and risks of tokenistic engagement. The study concludes that architecture should be treated as governance infrastructure, public spaces must be planned, designed, and managed through participatory frameworks, co-governance mechanisms, and justice-oriented design guidelines so that governance principles are materially experienced in everyday urban life.